2017
DOI: 10.1128/aem.01075-17
|View full text |Cite
|
Sign up to set email alerts
|

Bacillomycin D Produced by Bacillus amyloliquefaciens Is Involved in the Antagonistic Interaction with the Plant-Pathogenic Fungus Fusarium graminearum

Abstract: (teleomorph: Ascomycota, Hypocreales, ,) is a destructive fungal pathogen that threatens the production and quality of wheat and barley worldwide. Controlling this toxin-producing pathogen is a significant challenge. In the present study, the commercially available strain (, ,, ) FZB42 showed strong activity against The lipopeptide bacillomycin D, produced by FZB42, was shown to contribute to the antifungal activity. Purified bacillomycin D showed strong activity against , and its 50% effective concentration w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
145
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 207 publications
(161 citation statements)
references
References 55 publications
16
145
0
Order By: Relevance
“…SPE70, SPE80, SPE90 and SPE100: fraction eluted with 70, 80, 90 and 100% methanol from SPE C 18 and the same letter means do not differ statistically (P < 0Á05) by Duncan tests. strong antifungal activity against Fusarium graminearum (Gong et al 2015), Botryosphaeria dothidea (Li et al 2016) and Botrytis cinerea (Zhang et al 2013), among others; surfactin analogues demonstrate high levels of suppressive activity against Fusarium oxysporum (Gu et al 2017), Fusarium moniliforme (Jiang et al 2016;Sarwar et al 2018), R. solanacearum (Xiong et al 2015), among others. In this study, the LP mixture (iturin, fengycin and surfactin) yielded by B. amyloliquefaciens strain FJAT-2349 could effectively inhibit the growth of R. solanacearum.…”
Section: Discussionmentioning
confidence: 99%
“…SPE70, SPE80, SPE90 and SPE100: fraction eluted with 70, 80, 90 and 100% methanol from SPE C 18 and the same letter means do not differ statistically (P < 0Á05) by Duncan tests. strong antifungal activity against Fusarium graminearum (Gong et al 2015), Botryosphaeria dothidea (Li et al 2016) and Botrytis cinerea (Zhang et al 2013), among others; surfactin analogues demonstrate high levels of suppressive activity against Fusarium oxysporum (Gu et al 2017), Fusarium moniliforme (Jiang et al 2016;Sarwar et al 2018), R. solanacearum (Xiong et al 2015), among others. In this study, the LP mixture (iturin, fengycin and surfactin) yielded by B. amyloliquefaciens strain FJAT-2349 could effectively inhibit the growth of R. solanacearum.…”
Section: Discussionmentioning
confidence: 99%
“…Cell viability and cellular integrity were measured by PI staining, as described previously (10, 22). To produce M.…”
Section: Methodsmentioning
confidence: 99%
“…Many results have shown that iturin can inhibit the mycelium growth of many fungi, including Candida albicans , Aspergillus flavus , Sclerotinia sclerotiorum , Botrytis cinerea , Monilinia fructicola , Fusarium graminearum and so on(1821). More specifically, iturin extracted from Bacillus amyloliquefaciens FZB42 could cause morphological changes in the plasma membranes and cell walls of F. graminearum hyphae, lead to ROS accumulation, and induce cell death in conidia (22). When iturin was used against S. sclerotiorum , it could also trigger a separation of cell walls from membranes and even form a pore in the cell membrane, resulting in leakage of the cytoplasm(19).…”
Section: Introductionmentioning
confidence: 99%